2013
DOI: 10.1371/journal.pone.0074262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Smoking Status Identification Using Electronic Health Records and Open-Text Information in a Large Mental Health Case Register

Abstract: BackgroundHigh smoking prevalence is a major public health concern for people with mental disorders. Improved monitoring could be facilitated through electronic health record (EHR) databases. We evaluated whether EHR information held in structured fields might be usefully supplemented by open-text information. The prevalence and correlates of EHR-derived current smoking in people with severe mental illness were also investigated.MethodsAll cases had been referred to a secondary mental health service between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 30 publications
3
59
3
Order By: Relevance
“…Fourth, while we adjusted our obesity and smoking estimates for nonresponse to reduce the impact of data missing differentially across strata, doing so did not change the obesity estimate and only changed the smoking estimate by 0.01 percentage points. Fifth, contrary to our expectation and findings from Wu et al,56 our chart review of 48 EHRs found that scanning unstructured fields only minimally improved indicator sensitivity. This finding is important and reassuring because natural language processing to extract unstructured data is not possible within NYC Macroscope and is complicated and burdensome in any setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Fourth, while we adjusted our obesity and smoking estimates for nonresponse to reduce the impact of data missing differentially across strata, doing so did not change the obesity estimate and only changed the smoking estimate by 0.01 percentage points. Fifth, contrary to our expectation and findings from Wu et al,56 our chart review of 48 EHRs found that scanning unstructured fields only minimally improved indicator sensitivity. This finding is important and reassuring because natural language processing to extract unstructured data is not possible within NYC Macroscope and is complicated and burdensome in any setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Other natural language-processing applications developed in the Clinical Record Interactive Search system in current research use include those ascertaining text on tobacco 22 and cannabis use, 23 medications for diabetes and other physical disorders, 7 and more than 70 different mental health symptoms 24 . These efforts have been supplemented by a range of new algorithms for ascertaining recorded body-mass index and mentions of comorbid physical disorders and use of several common illicit drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, smoking has been found to be under-reported in EHRs, so using only structured smoking fields to characterize patients may inaccurately identify current and former smokers. 56 While illuminating to the analysis, geocoding patient data presents its own set of challenges. Some patients had missing or inaccurate address data, forcing us to drop them from this portion of the analysis.…”
Section: Discussionmentioning
confidence: 99%